Sporadic adenoma or ulcerative colitis associated neoplasia? The endoscopist's information has an impact on diagnosis and patient management - Lang-Schwarz, Corinna; Adler, Werner; Geppert, Michael; Seitz, Gerhard; Sterlacci, William; Falkeis-Veits, Christina; Veits, Lothar; Drgac, Jan; Melcher, Balint; Lang-Schwarz, Klaus; Nikolaev, Svetlana; Dregelies, Theresa; et al. (Pathology Research and Practice, 2020)
Background: Diagnosing low grade intraepithelial neoplasia (LGIN) in patients with ulcerative colitis (UC) is difficult. Distinguishing between sporadic adenoma (SA) and UC associated LGIN is even more challenging but has clinical impact. We aimed to examine, if the morphological distinction between both entities is reliably possible, how it influences patient's outcome and the role of the endoscopist in this decision with respect to current endoscopy classification schemes. Methods: Seven pathologists retrospectively reevaluated 425 cases of LGIN in UC patients, diagnosed between 2009 and 2017 with preceding expert consensus and follow up in two separate readings, based on published morphological differentiation criteria. In the first evaluation, the observers were blinded to any clinical data. In the second evaluation, they knew patients’ age as well as endoscopic features. They also rated their subjective diagnostic certainty. Results: Diagnostic correctness improved significantly in the second assessment as did the pathologists’ confidence in their diagnoses (p < 0.001 - p = 0.019). Knowledge of clinical and endoscopical data led to a higher percentage of SA (71.8% vs. 85.6%). UC associated LGIN showed significant earlier LGIN relapse as well as more high grade intraepithelial neoplasia and carcinoma during follow up (p < 0.001, p < 0.001, p = 0.005). Conclusions: Distinction between SA and UC associated LGIN is important as it has an impact on patients’ follow up and treatment. Morphological distinction remains difficult with moderate interobserver variability. Adequate clinical information significantly improves pathologists’ diagnoses as well as their confidence in their diagnoses.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Low grade intraepithelial neoplasia; Sporadic adenoma; Ulcerative colitis